Crafting Strategy to Improve XYZ Rice Milling Business Competitiveness - Herasmara, Ridho; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
East Java rice milling business has been affected by a series of political policy regarding the industry, and increasing raw material purchase competition. This article is concerned about current competitive condition facing XYZ; it is experiencing problem of declining profitability even though the market is in uptrend. This decline is represented by problems in material purchase, production efficiency, and low selling price. The study and is aimed towards improving XYZ competitiveness and profitability. The literature review provided some generic framework in analyzing business condition and developing strategy (Wheelen & Hunger, 2012). Research is conducted by interviewing, observation of XYZ owner, and through secondary data gathering. Result of the research is analyzed to determine elements of business environment affecting XYZ. External analysis of the company point out strategic factors potentially important to the company such as market requirement of premium rice, differing price between east and west jave, as well as notable price discrepancy between area in East Java. Internal analysis of XYZ point out important strategic factors that affect XYZ in terms of its competitiveness, such as the relatively outdated production method and low direct sales effort of XYZ. From SWOT analysis of these factors, it is concluded that problem affecting XYZ competitiveness is requirement for reformulating business strategy. Based on it, a strategy is formulated for XYZ to improve competitiveness by upgrading production machinery, improve material purchase, and increase direct sales. It is concluded that the main problem of XYZ is low efficiency, and it is recommended that XYZ implement the solution to improve its competitive readiness and to prepare for future challenge.Ã‚Â Keywords: business strategy, rice milling business, business model, TOWS matrix